Factors associated with client satisfaction and implementation challenges for community-based health insurance in Ethiopia: beneficiaries' perspectives - Negesse, Habtamu; Negese, Tarekegn; Assalf, Shewayirga; Oumer, Abdu; Nuredin, Kedir; Reshid, Tewkel; Roba, Kedir Teji (Frontiers in Public Health, 2025)
BackgroundCommunity-based health insurance (CBHI) is implemented in Ethiopia to enhance healthcare access and provide financial risk protection for the vulnerable people. However, it falls short in fulfilling customers' needs and could be challenged by potential constraints, needing further investigation. This study was to assess factors associated with client satisfaction and implementation challenges for CBHI in Ethiopia.MethodsA mixed-methods (quantitative and qualitative) survey was employed using face-to-face interviews combined with key informant interviews (KII) using appreciative inquiry to learn more about the practice of CBHI. The quantitative part employed structured questionnaires, and interviews were conducted among a random sample of 782 CBHI beneficiaries using the pretested and validated Ethiopian Health Insurance Agency (EHIA) tool holding multiple dimensions, to measure client satisfaction level and quality. In addition, KII was conducted with 16 key informants from program implementer and facility planning units. The data were analyzed and presented in descriptive statistics. The KII were transcribed, translated, and analyzed using descriptive narrative analysis.ResultsA total of 782 CBHI beneficiaries with mean age of 47.6 (±11.6) years and 60.4% females were interviewed. With regard to dimensions of satisfaction, 74.3% reported that CBHI supported services at health facilities are accessible while 67.1% have trust in the health system and 61% reported to get quality services. Almost all were satisfied with the opening hours for service and information provided about the CBHI program. However, some respondents express dissatisfaction with the collection process and registration fee. Overall, about 32.4% (95% CI: 29.1–35.8) of the beneficiaries were satisfied with the CBHI services. CBHI implementation is at full scale in the area but its implementations are challenged by limited resource availability, administrative processes, insurance coverage, availability of essential services, and payments schemes. On the other hand, age (AOR = 3.66; 1.36–9.87), family size (AOR = 4.02; 2.13–7.59), education (AOR = 2.21; 1.34–3.66), and illness history (AOR = 3.15; 1.94–5.12) were associated with dissatisfaction with CBHI services.ConclusionOnly one-third of CBHI users were found to be satisfied with the service and it is associated with age, literacy, family size, and illness history. Key challenges cited include drug shortages, limited laboratory services, and bureaucratic policies, which should be addressed well.